ANALISIS FAKTOR LINGKUNGAN TERHADAP DISTRIBUSI JENIS TIKUS YANG TERKONFIRMASI SEBAGAI RESERVOIR LEPTOSPIROSIS DI TIGA KABUPATEN DI PROVINSI SUMATERA SELATAN - Yanelza Supranelfy; Nungki Hapsari S; Reni Oktarina (Balai Besar Penelitian dan Pengembangan Vektor dan Reservoir Penyakit (B2P2VRP) Salatiga, 2019)
The role of rats as a potential reservoir of the disease remains negative impacts on the routine life, safety, welfare and economic communities. Rattus tanezumi, R. norvegicus, R. exulans, R. hoffmani, R. argentiventer and Maxomys bartelsi have been confirmed as leptospirosis reservoirs in Indonesia. Some rat species suspected as leptospirosis reservoirs were reported in Lahat, Banyuasin and Ogan Komering Ilir (OKI) districts. It puts those three districts on high risk of leptospirosis transmission in the community. The aim of the study was to identify the environmental factors associated with the distribution of the leptospirosis-confirmed rats in the three districts of South Sumatera Province. Data used in this study were obtained from surveillance of the Specific Research on Vector and Reservoir Diseases Special Research